Review of the Role of Biomechanical Research in Developing Rehabilitation Physiotherapy Programs for Patients with Coxarthrosis - Hryshyn , Ivan; Antonova-Rafi, Julia (The Ukrainian Scientific Medical Youth Journal, 2023)
modern biomechanical research has introduced innovative possibilities for crafting rehabilitation physiotherapy programs. These investigations are transforming conventional approaches in designing rehabilitation physiotherapy programs for coxarthrosis treatment, leading to enhanced patient outcomes through pain reduction and improved quality of life. The objective of this study is to emphasize the contemporary application of biomechanical research in shaping rehabilitation physiotherapy programs for individuals with coxarthrosis. The following hypothesis is put forward within the framework of the raised issue: "Integration of biomechanical studies in the development of rehabilitation physiotherapy programs for patients with coxarthrosis will have a positive effect in the development of rehabilitation personal software techniques". The article anticipates the application of synthesis and analysis methods aimed at a comprehensive study of the role of biomechanical research in the development of effective physiotherapy rehabilitation programs for patients. The analysis and synthesis of scientific literature in the review article serve not only to summarize existing data but also to form a new level of understanding of the problem, which is an important step in improving clinical practice and developing new physiotherapy methods. Based on the specified methods, an analysis is being conducted to identify challenges in the implementation of biomechanical research methods and explore potential solutions within the framework of monitoring the outcomes of physical therapy in the treatment of coxarthrosis. Conclusion − examining the role of biomechanical research in rehabilitating patients with coxarthrosis is justified in terms of addressing the relevance of the issue and outlining the contemporary need for effective treatment methods, increased objectivity and quality of rehabilitation, and the search for ways to improve the quality of life for patients. During this review, it was established that biomechanical research of rehabilitation physiotherapy programs for coxarthrosis is an important method for evaluating the effectiveness of these programs.